Antioxidant Activity Test of Ethanol Extract of Feather Plantain Fruit (Musa paradisiaca L) with the DPPH Method (1,1- Diphenyl-2-Picrylhydrazyl) - Syahidatu, Dila; Firgiani, Gini; Ismail, Rian; Wahlanto, Panji (LPPM STIKes Muhammadiyah Ciamis, 2024)
Antioxidants are compounds that can counteract or reduce the negative effects of free radicals. Antioxidants work by donating one electrons to compounds that are free radicals so that the activity of these compounds can be inhibited. This study aims to determine the activity and potential of antioxidants in the extract of banana feather fruit (Musa paradisiaca) which is taken from the village of Gunungcupu, Ciamis Regency. This feather plantain extract is obtained by maceration extraction using 70% ethanol. The antioxidant potential in this study was measured using the DPPH (1,1-diphenyl-2-picrylhydrazyl) method by Uv-Vis spectrophotometry. The antioxidant activity of feather plantain extract and vitamin C were used as positive controls at concentrations of 10 ppm, 20 ppm, 30 ppm, 40 ppm, 50 ppm and 60 ppm. Absorbance measurements using Uv-Vis spectrophotometry at a maximum wavelength of 520 nm. The plantain feather extract has an IC50 value of 59.10 ppm. While vitamin C has an IC50 value of 73.20 ppm. Based on the classification of antioxidants strength, feather plantain extract and vitamin C have strong antioxidant activity.